PERENCANAAN JAMINAN KESEHATAN NASIONAL (JKN) DI PUSKESMAS BALAI JAYA KABUPATEN ROKAN HILIR TAHUN 2016-2017 - Jannah, Nur; Wicaksono, Baskoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The Social Security Administering Body (BPJS) is a legal entity established to organize a social security program. Participants of the Social Secu rity Administering Body (BPJS) Health is divided into 2 groups based on the origin of the financing. The first group is the Contribution Beneficiary (PBI), participants in the category of those who have difficulties in the economy. The second group of BPJS Health participants are those who belong to the Non-PBI class (Beneficiary of Contribution). Puskesmas Balai Jaya is a First Level Health Facility (FKTP) as a Technical Implementation Unit under Public Health Service that performs non-specialist personal health services for observation, diagnosis, treatment, treatment and or other health services. The problem formulation in this study is why the management of the National Health Insurance (JKN) budget by the Social Security Administering Agency (BPJS) of Health at Puskesmas Balai Jaya Rokan Hilir Regency is not maximal.The purpose of this study is to find out the National Health Insurance (JKN) planning at Balai Jaya Community Health Center 2016-2017. This research method using qualitative approach with descriptive research type.The results of this study indicate that the planning of National Health Insurance (JKN) in Puskesmas Balai Jaya Rokan HilirDistrict in 2016-2017 has not been done properly. It is based on the still many people who have not been integrated into the National Health Insurance (JKN). Based on Permensos Number 170 of 2015 the participant quota of JKN PBI Rokan Hilir 184,419 people, but for the year 2017 participants JKN PBI Rokan Hilir only 1,762 inhabitantsKeywords: Planning, National Health Insurance (JKN), BPJS Health